Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Melalui Penerapan Model Pembelajaran Problem Based Learning Pada Mata Pelajaran Matematika Kelas 1 SD Negeri 6 Pajar Bulan - Erawati, Desi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this research is to increase student motivation and learning outcomes through the application of the problem based learning model in grade 1 mathematics at SD Negeri 6 Pajar Bulan. The research carried out was Class Action Research (PTK) in 2 cycles. Each cycle consists of two meetings. The stages of each cycle are planning, implementation, observation and reflection. At each meeting, a pre-test and post-test are carried out to determine the students' progress. In cycle II, 76% of students completed the post test. In cycle II, 92% of students completed the post test. These results show that the Problem Based Learning (PBL) learning model can increase student motivation and learning outcomes, especially in class I mathematics subjects at SD Negeri 6 Pajar Bulan.